Learners' Experiences of Peer Tutoring in the Context of Outdoor Learning: The Case of a Primary School - Tšepo Mokuku; Likengkeng Ramakhula; Mantoetse Jobo (Environmental Association of Southern Africa, 2013)
The article explores peer tutoring in the context of outdoor learning at a primary school in Lesotho. The peer-tutoring approach was trialled to explore its effectiveness in promoting learning in large class sizes which characterise primary and secondary schools in Lesotho. An urban primary school was purposively selected for the study. The study involved 104 Class 6 learners as tutors, 86 Class 2 learners as tutees, and 8 teachers as facilitators. To determine the learners' perceptions on the peer tutoring and outdoor activities, focus-group discussions were employed. It is concluded that both the tutors and tutees responded positively to the outdoor learning activities and peer tutoring, but that the approaches need to be investigated further to establish tutor and tutee processes of interaction.